Age estimation in children by measurement of open apices in tooth roots: Study of a Mexican sample. - De Luca S; De Giorgio S; Butti AC; Biagi R; Cingolani M; Cameriere R; De Luca, Stefano; De Giorgio, Stefania; Butti, Andrea Carlo; Biagi, Roberto; Cingolani, Mariano; Cameriere, Roberto (Forensic Science International, 2012)
The aim of this cross-sectional study was to test the accuracy of Cameriere's European formula for age assessment in a large sample of Mexican children. The accuracy of dental age estimation was defined as how closely real age, measured as the difference between chronological age (CA) and dental age (DA), could be predicted. Digitalized orthopantomographs of 502 Mexican children (254 girls and 248 boys), aged between 5 and 15 years, were analyzed. The seven left permanent mandibular teeth were evaluated using Cameriere's method. Intra- and inter-observer variability for this technique was tested on a small random sample. Dental age was estimated for each individual and compared with known chronological age. Accuracy was measured as the difference between known chronological age and dental age and tested for significance with the mean prediction error (ME). The standard deviation and 95% confidence interval of the mean difference were also calculated. ME was 0.63 years for girls and 0.52 years for boys. ME was found to be slightly overestimated by 0.10 years for girls, but was correctly estimated for boys with an accuracy of 0.00. In conclusion, this method is very useful and may be recommended for practical application both in clinical dentistry and forensic procedures on the Mexican population.